Growth of oil palm (Elaeis guineensis) seedlings on acid sulfate soils as affected by water regime and aluminium - Auxtero, Edgardo A.; Shamshuddin, J. (Springer, 1991)
In Malaysia, acid sulfate soils contain high amounts of aluminium and are usually utilized for oil palm cultivation. As these soils are frequently flooded during rainy periods, it is thought that this may affect the growth performance of the oil palm. A glasshouse experiment was, therefore, conducted to study the effects of water regime and aluminium on the growth of oil palm seedlings. Soils used in the experiment were Typic Sulfaquepts and Sulfic Tropaquepts from Pulau Lumut Island, Malaysia. Best growth was observed on a non-jarositic freely drained topsoil. Oil palm seedlings were found the be moderately tolerant to soil acidity. Growth was only affected if Al3+ and Alsum activities in the soil solutions were above 100 and 700 μ M, respectively. Root length was found to be one of the better parameters to predict crop growth, while others included plant height, fron length and LAI. Soil solution attributes which could be used as indices of soil acidity for oil palm growth were pH and activities of Al3+, AlSO4+ and Alsum.